Multipurpose soft contact lens care in Japan - Toshida H (Dove Medical Press, 2012)
Hiroshi Toshida1,2, Yoshiaki Kadota3, Chikako Suto2, Toshihiko Ohta1, Akira Murakami21Juntendo University Shizuoka Hospital, Department of Ophthalmology, Shizuoka, 2Juntendo University School of Medicine, Department of Ophthalmology, Tokyo, 3Bausch & Lomb Japan Co, Ltd, Research and Development, Tokyo, JapanPurpose: To assess the use of multipurpose lens care products via an online survey conducted among soft contact lens (SCL) wearers in Japan.Methods: The subjects were 1000 men and women aged 15–44 years who reported that they cleaned their SCL by using multipurpose solution at least twice a week. Via the internet, they were asked questions about SCL care, the use of a rubbing step when cleaning SCL, cleaning and replacing lens cases, and recommended SCL care methods.Results: Of the 1000 SCL wearers enrolled, 94.3% performed lens care every day lenses were worn, 64.2% reported rubbing the lenses every time, 57.9% rubbed the lenses for at least 10 seconds per side, and 64.7% reported they rubbed the lenses on both sides. Further, 61.2% reported that they had been given an explanation of SCL cleaning at an eye clinic or contact lens store. Only 49.8% of subjects reported that they cleaned the lens case every time and 61.7% replaced the case within 3 months. Only 19.5% had been given an explanation about lens case care. Half of the subjects reported they had been given no recommendation to use specific SCL care products or could not remember whether or not they had. The most common reason for the recommendation was good compatibility with their type of lens.Conclusion: More education is needed in Japan regarding methods of SCL care to ensure correct lens cleaning with inclusion of a rubbing step, as well as sufficient cleaning and replacement of the lens case. Of particular interest is the finding that many subjects were not given an explanation about proper SCL care and lens case cleaning and replacement at the time of lens purchase or prescription.Keywords: soft contact lens, multipurpose solutions, compliance, questionnaire survey, contact lens care